The Seismic Moment and Seismic Efficiency of Small Impacts on Mars - Wójcicka, N.; Collins, G.S.; Bastow, I.D.; Teanby, N.A.; Miljkovic, Katarina; Rajšić, Andrea; Daubar, I.; Lognonné, P. (AMER GEOPHYSICAL UNION, 2020)
Since landing in late 2018, the InSight lander has been recording seismic signals on the surface of Mars. Despite nominal prelanding estimates of one to three meteorite impacts detected per Earth year, none have yet been identified seismically. To inform revised detectability estimates, we simulated numerically a suite of small impacts onto Martian regolith and characterized their seismic source properties. For the impactor size and velocity range most relevant for InSight, crater diameters are 1–30 m. We found that in this range scalar seismic moment is 106–1010 Nm and increases almost linearly with impact momentum. The ratio of horizontal to vertical seismic moment tensor components is ∼1, implying an almost isotropic P wave source, for vertical impacts. Seismic efficiencies are ∼10−6, dependent on the target crushing strength and impact velocity. Our predictions of relatively low seismic efficiency and seismic moment suggest that meteorite impact detectability on Mars is lower than previously assumed. Detection chances are best for impacts forming craters of diameter >10 m.